Role of cereal aphid in the epidemiology of Fusarium head blight in wheat - Asamoah, Samuel (2024)
Cereal aphids can play a significant role in the epidemiology of Fusarium head blight (FHB) by amplifying the reduction of the physiological and biochemical fitness of the host plant. However, little work has been done regarding the systemic effects of aphid feeding on the host and the compatibility of different aphid species with Fusarium graminearum for dispersal and pathogenesis. Therefore, the primary aim of the work presented in this thesis was to determine the ecological and epidemiological consequences of interactions between two different species of cereal aphids, Rhopalosiphum padi and Sitobion avenae and F.graminearum. This work investigated the aphids' pre- and post-alighting behavioural responses to Fusarium graminearum-infected wheat cultivars with contrasting disease resistance profiles. Results showed that alate R. padi was attracted to both FHB susceptible and resistant plants infected with DON-producing F. graminearum while S. avenae was repelled. One of the mechanisms of R.padi attraction was the release of distinct volatile emissions from FHB-infected hosts. However, sharing the host space with the pathogen resulted in the competitive exclusion of both aphids by F. graminearum because aphid fitness was reduced, as shown by decreased pest reproductive rates and increased mortality. In contrast, aphid activity on the shared ear niche resulted in enhanced pathogen fitness because disease severity and Fusarium mycotoxins, such as DON, substantially increased in both genotypes.